New economy—same irrational economy. - Tabb, William K. (Monthly Review: An Independent Socialist Magazine, 2001)
Part of a special issue on the new economy. The writer contends that it is wrong to claim that the business cycle has been eliminated by the new economy and that the information revolution does not change the basic way capitalism works. It is more important to recognize the continuity of the system and question whether a new economy exists and how it effects workers, consumers, and citizens.